Perspectives in Designing Multifunctional Molecules in Antipsychotic Drug Discovery. Issue 8 (19th August 2016) - Milelli, Andrea; Turrini, Eleonora; Catanzaro, Elena; Maffei, Francesca; Fimognari, Carmela
ABSTRACT: Preclinical Research A novel and promising approach to overcome the limits of single‐target therapy is represented by the multitarget approach. This strategy aims to simultaneously modulate several targets involved in the pathophysiology of a multifactorial disease, with the potential to enhance therapeutic effectiveness and improve drug safety. Although there has been a marked growth in the design of multitarget drugs (MTDs) in the last years in the context of anti‐Alzheimer and anti‐cancer drug discovery, a parallel expansion was not observed in antipsychotic drugs, even that for psychiatric disorders there is a cogent medical need for new treatments. The discovery of new MTDs is a challenging task and we will describe the main strategies that have been developed over the years for the design of multifunctional molecules in antipsychotic drug discovery. In particular, we will focus on the few available MTDs based on the design of selective serotonin re‐uptake inhibitors, used as antidepressants and in the treatment of schizophrenia. Drug Dev Res 77 : 437–443, 2016. © 2016 Wiley Periodicals, Inc.